PENGKAJIAN TUMBUH KEMBANG BALITA MELALUI DDTK /DENVER - Fatsiwi Nunik Andari; M. Bagus Andrianto; Leni Rozani; Andri Kusuma Wijaya (JURNAL PENGABDIAN KESEHATAN, 2022)
ABSTRACT The golden age period or what is often termed the golden age is a vital period for children aged 1-6 years in terms of growth and development Sado. This period made a great contribution to the stages of further development of the child. Growth is the time when it happens increase in the number and size of human body cells, while the development of focuses more on changes that occur gradually through the process maturation and learning. Development is closely related to growth where the two cannot be separated in the assessment of toddler growth and development. Many factors influence the growth and development of toddlers, including hereditary factors, environment, culture, family socioeconomic status, parenting and internal factors such as the child's level of intelligence. Development toddlers will also be reflected in the behavior they show in their abilities activity or sensory motor and speech abilities or toddler interactions with children things around him. This growth and development can be assessed by using the DDTK or Denver measuring instrument. This service activity is carried out with the aim of knowing growth and development of toddlers in RT 17 RW 06, Sido Mulyo Sub-district, District Ivory City Bengkulu. From the results of the evaluation of activities, it is obtained an overview of growth normal toddler development or according to his age. Keywords: DDTK, Denver, Growing Up, Toddler.